Do The Children Need To Learn English at Elementary Level ? - Hardi, Vitri Angraini; Marleni, Lusi (Universitas Pahlawan Tuanku Tambusai, 2020)
This aim of this research is to provide an insight on English as foreign language learning at elementary school level. Since the English is learned as foreign language in Indonesia, the shifting of English in Indonesia curriculum is one of the interested research focus. It is explicitly declared in Curriculum 2013 that English is taught as an extracurricular subject in Indonesia elementary school. The government does not obligate the elementary students to learn English. The elementary schools have an opportunity to decide English to be included as a subject in the curriculum. The shifting of the governmentâ€™s consideration in deciding the starting focus of English learning at junior high school level is the maturity level of learners in learning a foreign language. Dealing with the stated focus, a critical overview on the foreign language learning is conducted. Several research reported that learning a foreign language is better to be started at the early age because of the early age students are easier to imitate the new language. The way of thinking in imitating stages is assumed as the best time to start learning a foreign language. In another point, several research reported that maturity level of learners is the essential point to be considered because learning a foreign language need is not only imitating the language but also understanding the culture, combining linguistics aspects and so on. Despite the fact on the different views of scholars, both of the parties agree on the focus of learning a language is not a matter of age. The contributions of several factors are also part of the supported system in learning foreign language. In term of English foreign language learning, different age-level have to be given different learning input. An early age students should be given speaking and listening topics due to the students do not involve the critical thinking process. Meanwhile, the mature students are better to be provided reading and writing topic due to the depth thinking phase is in theirs.Â